1993
DOI: 10.1002/bjs.1800801238
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colorectal surgery: A prospective assessment and current perspective

Abstract: Between August 1991 and June 1993, 74 laparoscopic and laparoscopically assisted colonic and rectal operations were performed. A variety of procedures were carried out including 32 total abdominal colectomies (group 1), 32 segmental resections (group 2) and ten constructions of a diverting stoma without formal resection (group 3). Indications for surgery were mucosal ulcerative colitis in 20 patients, carcinoma in 12, polyposis in six, Crohn's disease in seven and other conditions in the remaining 29. The 74 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(54 citation statements)
references
References 10 publications
1
51
1
1
Order By: Relevance
“…Dies gilt noch in weit ho È herem Maûe fu È r Patienten mit malignen Grunderkrankungen [27,47]. Bei der Beurteilung von Studien muû das Problem «Lernkurve» zunehmende Beru È cksichtigung finden [28,48]. Die Quantifizierung dieses Pha È nomens ist ein schwieriges Unterfangen, allerdings ist zumindest seine orientierende Abscha È tzung zur Qualita È tsbeurteilung unabdingbar.…”
Section: Spezielle Indikationen Der Laparoskopischen Kolorektalen Chiunclassified
“…Dies gilt noch in weit ho È herem Maûe fu È r Patienten mit malignen Grunderkrankungen [27,47]. Bei der Beurteilung von Studien muû das Problem «Lernkurve» zunehmende Beru È cksichtigung finden [28,48]. Die Quantifizierung dieses Pha È nomens ist ein schwieriges Unterfangen, allerdings ist zumindest seine orientierende Abscha È tzung zur Qualita È tsbeurteilung unabdingbar.…”
Section: Spezielle Indikationen Der Laparoskopischen Kolorektalen Chiunclassified
“…It does not have the same theoretical advantages as a laparo scopic cholecystectomy, because the 'access trauma' is a smaller proportion of the total 'operative trauma', and an abdomoinal inci sion is required to remove the bowel speci men. It is, therefore, not surprising that some authors have found no substantial difference in the rates of postoperative recovery after the laparoscopic procedure [124,125]. In cancer resections, there is debate as to whether the laparoscopic approach is oncologically sound.…”
Section: Laparoscopic Colonic Proceduresmentioning
confidence: 99%
“…In the series of Wexner et al [124] of 74 pro cedures, 4 patients developed intra-abdomi nal abscesses (2 from accidental enterotomies and 2 from anastamotic leakage) and 4 re quired open surgery for major haemorrhage (2 trocar injuries to epigastric vessels, 1 Veress needle injury to the aorta, and 1 iliac injury from dissection). There are anecdotal reports of ureteric injuries.…”
Section: Laparoscopic Colonic Proceduresmentioning
confidence: 99%
“…Operative complications such as major haemorrhage, inadvertent enterotomy, ureteral injury, and major vessel laceration have all been reported, with rates ranging from 0 to 12% [6, 12, 14, 46, 51, 56, 57, 59]. The overall morbidity rate is between 6 and 39% [59,68,69,70,71,72,73,74,75,76,77]. …”
Section: Complicationsmentioning
confidence: 99%